Gene microarray integrated with iTRAQ-based proteomics for the discovery of NLRP3 in LPS-induced inflammatory response of bovine mammary epithelial cells. Issue 4 (14th November 2019) - Sun, Yu; Li, Lian; Li, Chengmin; Wang, Genlin; Xing, Guangdong
Abstract: Mastitis, a major infectious disease in dairy cows, is characterized by an inflammatory response to pathogens such as Escherichia coli and Staphylococcus aureus . To better understand the immune and inflammatory response of the mammary gland, we stimulated bovine mammary gland epithelial cells (BMECs) with E. coli -derived lipopolysaccharide (LPS). Using transcriptomic and proteomic analyses, we identified 1019 differentially expressed genes (DEGs, fold change ≥2 and P -value < 0.05) and 340 differentially expressed proteins (DEPs, fold change ≥1.3 and P -value < 0.05), of which 536 genes and 162 proteins were upregulated and 483 genes and 178 proteins were downregulated following exposure to LPS. These differentially expressed genes were associated with 172 biological processes; 15 Gene Ontology terms associated with response to stimulus, 4 associated with immune processes, and 3 associated with inflammatory processes. The DEPs were associated with 51 biological processes; 2 Gene Ontology terms associated with response to stimulus, 1 associated with immune processes, and 2 associated with inflammatory processes. Meanwhile, several pathways involved in mammary inflammation, such as Toll-like receptor, NF-κB, and NOD-like receptor signaling pathways were also represented. NLRP3 depletion significantly inhibited the expression of IL-1β and PTGS2 by blocking caspase-1 activity in LPS-induced BMECs. These results suggest that NLR signaling pathways works in coordination with TLR4/NF-κB signaling pathways via NLRP3-inflammasome activation and pro-inflammatory cytokine secretion in LPS-induced mastitis. The study highlights the function of NLRP3 in an inflammatory microenvironment, making NLRP3 a promising therapeutic target in Escherichia coli mastitis.